Quantitative immunohistologic assessment of lymphocyte populations in the pulmonary inflammatory response to intratracheal silica. - Kumar, R. K. (1989)
Immunogold-silver staining was used to identify T lymphocytes, T lymphocyte subsets, and B lymphocytes in lung tissue from mice injected intratracheally with silica, titanium dioxide, or saline alone. Morphometric quantitation revealed a marked influx of T lymphocytes in the silica-treated animals during the first 3 weeks after injection. The relative numerical density of these cells remained elevated when compared with saline-treated controls throughout the 12 weeks of the experiment. Cells expressing the CD4 and CD8 antigens were both increased in number, with the former accounting for approximately two-thirds of the T lymphocytes. An increased number of B lymphocytes was also apparent from 6 weeks after treatment with silica. The T lymphocyte response preceded the development of significant pulmonary fibrosis by several weeks. No lymphocyte response was observed in the lungs of mice injected with nonfibrogenic titanium dioxide. These observations are consistent with the hypothesis that lymphokines secreted by T lymphocytes play a role in the pathogenesis of silicotic inflammatory lesions and their progression to fibrosis.